Sustainability Challenges of the Mid-nineteenth-century Dutch Energy System - Hölsgens, Rick (TSEG - The Low Countries Journal of Social and Economic History, 2016)
Energy consumption plays a central role in sustainability debates. However, how new are these sustainability challenges? Did sustainability challenges feature in historical energy transitions? This paper analyses societal debates concerning sustainability around the transition from peat to coal in the Netherlands in the mid-nineteenth century. By dividing sustainability challenges in here and now, later and elsewhere, this paper addresses to which extent elements of sustainable development featured in the historical resource transition. Digitized publications in newspapers and journals were analysed using discourse analysis in order to trace back the existence of themes related to sustainable development. Elements of the modern-day discussions can indeed be found in the contemporary discussion. Secondly the paper shows why contemporaries made certain choices that later caused new sustainability challenges. Many of our current energy-related challenges may find their origin in the nineteenth century; it is nevertheless unjust to blame them on these generations.